RESISTANCE AND CRITIC AGAINST BOURGEOISIE IN WIDJI THUKUL’S POEM “BUNGA DAN TEMBOK” - Lesmana, Yogi Wijaya; Zahraniarni; Izfadlillah, Thesa (ReALL - Research on Applied Linguistics and Literature, 2024)
Understanding Indonesian poetry from the New Order Period offers important insights on the social, economic and political situation of that period. "Bunga dan Tembok," one of Widji Thukul's well known poems, provides a critical lens of the socioeconomic difficulties that the working class experienced. Although Widji Thukul's poetry has been the subject of multiple studies, it appears that there has not yet a specific examination of his works using a Marxist approach. This study looks at "Bunga dan Tembok" from a Marxist angle in an attempt to close this gap. Using Marxist concepts, the main goal of this study is to reveal the socioeconomic situation interpretations in "Bunga dan Tembok" by Widji Thukul. This study uses Marxist concepts of alienation and the class system shown in the poem to analyze how the poet responded to the reality of the New Order era. The study used a qualitative methodology, with an emphasis on a detailed textual examination. Marx’s concepts acted as theoretical foundations to direct how the poem's content was interpreted. This result highlighted the social inequality between the proletariat and the bourgeoisie during Indonesia's New Order regime. It illustrated how the working class experienced alienation from their land, labor, and humanity due to exploitation and repression by the ruling elite. Despite these challenges, the poem conveyed a sense of class consciousness and the potential for resistance among the marginalized people, suggesting that they could reclaim their humanity and challenge the oppressive system. The symbol of “Bunga” represented this proletariat resistance, emphasizing their ability to rise against the forces that alienated them.